(untitled) (Research, Society and Development, 2022)
The study has as its object violence against women in the shadow of the Public Power in contemporary times. The hypothesis is that the operational disorganization of public policies and the lack of an adequate investigative structure generate the concealment of gender crimes. The objective of this study was to discuss the relevance of feminicide classification for the improvement of public policies on human rights, health, and women’s promotion in the metropolitan region of the State of Rio de Janeiro, in conjecture of the invisibility of feminicides in a scenario of structural deficiency. In this context, it is highlighted that patriarchal domination is the background to explain the structural situation of inequality that inferiorizes and subordinates’ women to men, feeds the feelings of control and possession over the female body, justifies the feeling of contempt for the condition of female social condition, factors that influence these deaths. Based on the survey and analysis of data from 2019 to 2021, it is concluded that there are flaws in the efforts in the approach and investigation, these circumstances make invisible the real numbers of violence against women by gender, whose impact negatively affects the effectiveness of public policies of human rights, health, and promotion of women.